2021
DOI: 10.1371/journal.pone.0261623
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of 455 patients receiving the AFX2 endovascular graft for the treatment of abdominal aortic aneurysm: A retrospective multi-center analysis

Abstract: Since being introduced into clinical practice the AFX family of endografts has undergone labelling updates, design and manufacturing changes to address a Type III failure mode. The published literature on the performance of the current endograft–AFX2 –is limited to small series with limited follow up. The present study reports the largest series of patients implanted with AFX2 for the treatment of abdominal aortic aneurysms. The study was a retrospective, 5 center study of patients receiving an AFX2 endograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…This same study reported type III endoleak rates of 14.1% for AFX2 at 2 years post intervention, although these results were based on a cohort of only 33 patients. These results are in contrast to findings reported in a multicenter retrospective analysis sponsored by Endologix, which reported 2-year rates of type III endoleaks of 0.4% in a cohort of 405 patients. Our findings, based on 602 patients receiving AFX2 devices, fall in between, with a rate of type III endoleaks of 4.5% at 2 years.…”
Section: Discussioncontrasting
confidence: 99%
“…This same study reported type III endoleak rates of 14.1% for AFX2 at 2 years post intervention, although these results were based on a cohort of only 33 patients. These results are in contrast to findings reported in a multicenter retrospective analysis sponsored by Endologix, which reported 2-year rates of type III endoleaks of 0.4% in a cohort of 405 patients. Our findings, based on 602 patients receiving AFX2 devices, fall in between, with a rate of type III endoleaks of 4.5% at 2 years.…”
Section: Discussioncontrasting
confidence: 99%
“… 15 , 16 Following these investigations, multiple product design, manufacturing, and labeling updates were implemented, which led to significant improvement in the outcomes by a reduction in the incidence of aneurysm-related complications and a lower incidence of type III endoleaks using the DuraPly AFX stent compared with the Strata stent. 17 , 18…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the outcomes associated with the first generation of AFX (Strata) and have shown a high rate of Type IIIa/IIIb endoleak at three years 15,16 . Following these investigations, multiple product design, manufacturing, and labeling updates were implemented which led to a significant improvement of outcomes in terms of a reduction of aneurysm related complications, and of a lower incidence of type III endoleak with Duraply compared to Strata 17,18 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A recent study revealed excellent outcomes after using AFX with a low rate of type-III endoleaks. 11 In Japan, the latest version of the unibody stent graft (AFX2) was launched in February 2017.…”
Section: Introductionmentioning
confidence: 99%